Fundamentals of the use of Berberis as a medicinal plant - Bober, Zuzanna; Stępień, Agnieszka; Aebisher, David; Ożóg, Łukasz; Bartusik-Aebisher, Dorota (European Journal of Clinical and Experimental Medicine, 2018)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. The daily use of medicinal plants has increased in recent years. The study of drugs of natural origin as an academic discipline and its applications in healthcare has changed remarkably but still focus on the quality of products and the development of new medicines. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. This study covers all fundamental aspects of pharmacognosy as well as topics relating to the therapeutic use of plant drugs known as phythotherapy. The purpose of the study was to review the literature about the use of Berberis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. We reviewed the literature regarding the use of Berberis published between 1933 and 2018. We found more than 500 articles studying the properties of Berberis for digestive disorders, antibacterial, antidiabetic, hypotensive effects, anti-inflammatory effects, cholesterol regulation, cardiovascular disease, hyperlipidemia, cerebral ischemia trauma, mental disease, Alzheimer disease and osteoporosis. Our review includes recent studies regarding chemical composition and medicinal outcomes of Berberis.